Substance use and pre-hospital crash injury severity among U.S. older adults: A five-year national cross-sectional study. - Oluwaseun Adeyemi; Marko Bukur; Cherisse Berry; Charles DiMaggio; Corita R Grudzen; Sanjit Konda; Abidemi Adenikinju; Allison Cuthel; Jean-Baptiste Bouillon-Minois; Omotola Akinsola; Alison Moore; Ryan McCormack; et al. (PLoS ONE, 2023)
Background Alcohol and drug use (substance use) is a risk factor for crash involvement. Objectives To assess the association between substance use and crash injury severity among older adults and how the relationship differs by rurality/urbanicity. Methods We pooled 2017-2021 cross-sectional data from the United States National Emergency Medical Service (EMS) Information System. We measured injury severity (low acuity, emergent, critical, and fatal) predicted by substance use, defined as self-reported or officer-reported alcohol and/or drug use. We controlled for age, sex, race/ethnicity, road user type, anatomical injured region, roadway crash, rurality/urbanicity, time of the day, and EMS response time. We performed a partial proportional ordinal logistic regression and reported the odds of worse injury outcomes (emergent, critical, and fatal injuries) compared to low acuity injuries, and the predicted probabilities by rurality/urbanicity. Results Our sample consisted of 252,790 older adults (65 years and older) road users. Approximately 67%, 25%, 6%, and 1% sustained low acuity, emergent, critical, and fatal injuries, respectively. Substance use was reported in approximately 3% of the population, and this proportion did not significantly differ by rurality/urbanicity. After controlling for patient, crash, and injury characteristics, substance use was associated with 36% increased odds of worse injury severity. Compared to urban areas, the predicted probabilities of emergent, critical, and fatal injuries were higher in rural and suburban areas. Conclusion Substance use is associated with worse older adult crash injury severity and the injury severity is higher in rural and suburban areas compared to urban areas.